2018
DOI: 10.5688/ajpe6644
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simulations to Improve Pharmacy Students’ Knowledge, Skills, and Attitudes About Medication Errors and Patient Safety

Abstract: Objective. To design and evaluate the use of simulations to prepare students to identify and reduce medication errors and promote patient safety.Methods. Third year pharmacy students used methods of root cause analysis to determine the cause of a medication error in three simulated pharmacy settings. Prior to and following the activity, students were invited to complete an anonymous survey. Students were asked to complete a modified Healthcare Professionals Patient Safety Assessment instrument to measure chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
3
17
1
1
Order By: Relevance
“…To our knowledge, no previous studies have evaluated the impact of simulated rounds on changes in sepsis knowledge. Although previous studies have indicated that simulation exercises increase knowledge and skills, [9][10][11][12][17][18][19][20] our students did not show a statistically significant change in sepsis knowledge between the didactic lecture and simulation. This finding may be due to significant changes already being observed between the pre-and post-didactic lecture surveys as well as small sample sizes.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…To our knowledge, no previous studies have evaluated the impact of simulated rounds on changes in sepsis knowledge. Although previous studies have indicated that simulation exercises increase knowledge and skills, [9][10][11][12][17][18][19][20] our students did not show a statistically significant change in sepsis knowledge between the didactic lecture and simulation. This finding may be due to significant changes already being observed between the pre-and post-didactic lecture surveys as well as small sample sizes.…”
Section: Discussioncontrasting
confidence: 95%
“…Although not statistically significant, students demonstrated an overall increase in knowledge following the simulation activity. In 2018, Frenzel et al 12 investigated the use of simulations in preparing pharmacy students to identify and respond to medication errors. Following the simulation, students (n = 90) showed a statistically significant increase in overall knowledge assessment scores (p < 0.01).…”
mentioning
confidence: 99%
“…In the present study the simulation-based training improved the anesthetists' attitude significantly (P < 0.03) which is in line with a study done at a single pharmacy school campus in North Dakota State University which used root cause analysis to evaluate pharmacy students improvement in attitude to reduce medication error and promote patient safety [18]. The improvement in the posttest attitude score could be because the simulation-based sessions encouraged participants to actively engage in the real time patient care and during the debriefing session video analysis on what went well and what could have been improved were discussed.…”
Section: Discussionsupporting
confidence: 88%
“…State University which used root cause analysis to evaluate pharmacy students improvement in attitude to reduce medication error and promote patient safety(18) (18,19). The improvement in the posttest attitude score could be because the simulation-based sessions encouraged participants to actively engage in the real time patient care and during the debriefing session video analysis on what went well and what could have been improved were discussed.…”
Section: Discussionmentioning
confidence: 99%